Pemanfaatan Media Pemasaran Berbasis Website Profile Dan Katalog Digital Pada Warmindo 3 Sahabat - Arumsari; Saly Kurnia Octaviani; Ari Wibowo; Elistya Rimawati (Redtech Putra Benua, 2024)
Warmindo 3 Sahabat is one of the culinary businesses located in the city of Surakarta. One of the marketing media carried out to develop the business is by making marketing media based on website profiles and digital catalogs. The data collection method used is observation, interview and documentation. The results of the website profile and digital catalog are expected to be able to support the progress of Warmindo 3 Sabahat.